Application of topological concepts to the investigation of COVID-19 (modified) symptoms. Issue 7 (3rd October 2021) - Zyarah, Ali Abd Alhussein; Salman, Zahrah Ismael; Hashim Al Hakeem, Mohammed Baqer; Al-Mothafar, Noora A.; Hussain, Ahmed Hadi
Abstract: We examine 10 hypothetical patients suffering from some of the symptoms of COVID 19 (modified) using topological concepts on topological spaces created from equality and similarity interactions and our information system. This is determined by the degree of accuracy obtained by weighing the value of the lower and upper figures. In practice, this approach has become clearer.